Pembuatan Westafel Otomatis dengan Memanfaatkan Kondensasi AC sebagai Sumber Air - Rina Rina; Junaidi Junaidi; Rakiman Rakiman; Haris Haris; Sherly Septa Mirza (Jurnal Teknik Mesin, 2021)
The problem of Coronavirus disease (COVID-19) has not stopped. It was necessary to implement the Covid-19 protocol to avoid spreading, one of which is to wash hand regularly using and circulating water. Based on these reasons, it was still necessary to develop automatic hand washing equipment which is currently a primary need in public places, offices, and educational facilities. This study aims to modify the automatic sink using the Arduino Uno R3 microcontroller as a data processor and Ultrasonic HC-SR04 as a sensor; testing the function of the tool, namely automatic soap and water faucet, hand dryer, piezoelectric buzzer as an air level alarm, by utilizing the results of AC condensation as an water source. The results of this automatic sink modification can meet Covid-19 standards and can be used by all groups, especially schools and offices that have started to be active, so that with this tool it can reduce the spread of Covid-19. In addition, it is that the source of water from the condensation can be used as an alternative to water to save the current increasing use of PDAM water.